Temporary Workers in Peru - Leguía, Joaquín (1973)
This paper provides an analysis of the legal situation of temporary workers in Peru identifying the lack of a specific legal framework that distinguishes them from categories that, although different, are recognized under the same generic name. In this context, the author outlines the definition of a temporary worker and gathers the central characteristics of their work to differentiate them from seasonal, accidental, and substitute workers. With that said, the article presents the employee benefits they are entitled to, such as job stability, severance package and vacations, unionization, and social security. In addressing each of these, the author makes clarifications and criticisms related to the different treatment that legislation gives to temporary workers. In this vein, he proposes recommendations to improve the protection and rights of temporary workers, suggesting legislative adjustments to prevent potential abuses and promote fair and uniform treatment for this category of workers.